Significance of fluid retention, body mass index, and weight loss in patients with advanced cancer. Issue 3 (25th June 2020) - Amano, Koji; Maeda, Isseki; Ishiki, Hiroto; Miura, Tomofumi; Hatano, Yutaka; Oya, Kiyofumi; Sakashita, Akihiro; Ito, Satoko; Hiratsuka, Yusuke; Morita, Tatsuya; Mori, Masanori
Abstract: Background: Few studies have investigated the relationship between body mass index (BMI) and mortality or evaluated the prognostic validity of a grading system incorporating BMI and weight loss in Asian cancer patients. We conducted a study to investigate characteristics according to BMI and to confirm the prognostic validity of BMI and the grading system. Methods: This study involved a secondary analysis of a prospective cohort study. Subjects were divided into six BMI groups and five grades according to the grading system. Characteristics were compared between the six groups. We conducted time‐to‐event analyses using the Kaplan–Meier method, log‐rank test, and univariate and multivariate Cox regression analyses. Results: A total of 1094 patients were classified into six BMI groups: <17 ( n  = 244), 17–18.4 ( n  = 211), 18.5–19.9 ( n  = 192), 20–21.9 ( n  = 196), 22–24.9 ( n  = 161), and 25 ≤ ( n  = 90). Regarding oedema, the prevalence increased with BMI, being 70% the 25 ≤ group. The prevalence of pleural effusion and ascites were the highest in the 25 ≤ group. Median survival ranged between 18 and 22 days in the six groups. No significant differences were observed in survival rates among the six BMI groups (log rank P  = 0.83). No significant differences were observed in survival rates among the five grades (log rank P  = 0.25). Conclusions: The prevalence of fluid retention is high in patients with advanced cancer. BMI and weight loss appear to lose their prognostic significance among them.